A clinical study on alopecia areata - Ninama, Kishan; Mahajan, Rashmi; Bilimoria, F. E.; Vaghani, Ashvin (International Journal of Research in Dermatology, 2018)
Background: Alopecia areata (AA) is a common auto-immune condition, causing hair loss. This disease has limited treatment modalities. Through this study, comparison between established modalities of treatment such as oral mini pulse therapy, intralesional corticosteroids and platelet-rich plasma (PRP) as a newer modality has been done. The objective of the study was to evaluate the efficacy and safety of various treatment modalities in alopecia areata. Methods: 45 patients with alopecia areata presenting to the OPD of Dermatology, Dhiraj hospital, Pipariya were included in this study. It was conducted as a randomized prospective study for a period of 16 weeks. After taking informed consent, patients were randomly distributed into three treatment groups. Group 1 patients were treated with Tab. Betamethasone 0.1 mg/kg every Saturday and Sunday, Group 2 was treated with Inj. Triamcinolone acetonide 10 mg/ml for scalp and 2.5 mg/ml for eye brows and face was injected into deep dermis; Group 3 was treated with Dermaroller followed by application of activated platelet rich plasma (PRP). SALT score was calculated at first visit and 16 weeks. Regrowth was calculated using Mac Donald and Null Horis grading Scale at 16 weeks. Results: The SALT score reduced from 13.27 to 7.52 in Group 1, 13.93 to 8.16 in Group 2 and 42.32 to 21.12 in Group 3. Mean grade of regrowth of hairs observed was 3.47, 3.80, 2.93 in Group 1, 2, 3 respectively. The results were analysed using paired t test. Conclusions:Intralesional corticosteroids viz. triamcinolone acetonide still remains the first choice of therapy for AA in adults with limited involvement. Systemic corticosteroids give lower response than intralesional steroids. Platelet Rich Plasma (PRP) showed promising results, especially in children and in extensive involvement. Compared to other treatment modalities Inj. PRP is safe and with less side effects.